Information and communication technologies : a World Bank Group strategy (World Bank WashingtonUS, 2002)
Deals with the World Bank Group's rationale, role, and strategy in the information infrastructure sector. Examines information and communication technologies applications, education and the World Bank's knowledge initiatives. Discusses elements related to quality assurance processes.
Keywords: INFORMATION TECHNOLOGY